Penerapan model pembelajaran means ends analysis (mea) untuk meningkatkan keterampilan pemecahan masalah soal cerita pada siswa sd - Elizza Widyastuti; Siti Kamsiyati; Anesa Surya (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This research used to improve the problem solving skills in story question by applying the Means Ends Analysis learning model for students. This research uses a qualitative approach by Classroom Action Research (CAR). This classroom action research was conducted using two cycles. The subject of this research is student from fourth grade of SD Negeri Bumi I Surakarta in 2019/2020 academic year, which have 15 student. The techniques of collecting data are observation, interviews, documentation, and tests. The results of the problem solving skills test in each action have increased, in the first condition showed an achievement of 7% or as many as 1 student. In the first cycles in first meeting showed an achievement as much as 20% or 3 students and the second meeting as much as 40% or 6 students. In second cycles in first meeting showed an achievement as much as 67% or 10 students and in second meeting as much as 87% or 13 students. Based on this research, the researcher can conclude that by applying the Means Ends Analysis learning model can improve the problem solving skills in fourth grade of SD Negeri Bumi I Surakarta in 2019/2020 academic year.